Predictors of Nonseroconversion to SARS-CoV-2 Vaccination in Kidney Transplant Recipients. Issue 11 (7th October 2022) - Frölke, Sophie C.; Bouwmans, Pim; Messchendorp, A. Lianne; Geerlings, Suzanne E.; Hemmelder, Marc H.; Gansevoort, Ron T.; Hilbrands, Luuk B.; Reinders, Marlies E.J.; Sanders, Jan-Stephan F.; Bemelman, Frederike J.; Peters-Sengers, Hessel; ,
Abstract : Background: Kidney transplant recipients (KTRs) are still at risk of severe COVID-19 disease after SARS‑CoV‑2 vaccination, especially when they have limited antibody formation. Our aim was to understand the factors that may limit their humoral response. Methods: Our data are derived from KTRs who were enrolled in the Dutch Renal Patients COVID-19 Vaccination consortium, using a discovery cohort and 2 external validation cohorts. Included in the discovery (N = 1804) and first validation (N = 288) cohorts were participants who received 2 doses of the mRNA-1273 vaccine. The second validation cohort consisted of KTRs who subsequently received a third dose of any SARS-CoV-2 vaccine (N = 1401). All participants had no history of SARS-CoV-2 infection. A multivariable logistic prediction model was built using stepwise backward regression analysis with nonseroconversion as the outcome. Results: The discovery cohort comprised 836 (46.3%) KTRs, the first validation cohort 124 (43.1%) KTRs, and the second validation cohort 358 (25.6%) KTRs who did not seroconvert. In the final multivariable model‚ 12 factors remained predictive for nonseroconversion: use of mycophenolate mofetil/mycophenolic acid (MMF/MPA); chronic lung disease, heart failure, and diabetes; increased age; shorter time after transplantation; lower body mass index; lower kidney function; no alcohol consumption; ≥2 transplantations; and no use of mammalian target of rapamycin inhibitors or calcineurin inhibitors. The area under the curve was 0.77 (95% confidence interval [CI], 0.74-0.79) in the discovery cohort after adjustment for optimism, 0.81 (95% CI, 0.76-0.86) in the first validation cohort, and 0.67 (95% CI, 0.64-0.71) in the second validation cohort. The strongest predictor was the use of MMF/MPA, with a dose-dependent unfavorable effect, which remained after 3 vaccinations. Conclusions: In a large sample of KTRs, we identify a selection of KTRs at high risk of nonseroconversion after SARS-CoV-2 vaccination. Modulation of MMF/MPA treatment before vaccination may help to optimize vaccine response in these KTRs. This model contributes to future considerations on alternative vaccination strategies.